The Effect of Leadership Style on Managerial Performance Through Work Engagement and Innovative Work Behavior as Mediating Variables - Putra, Agung; Ng, Suwandi; Mardiana, Ana (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study aims to analyze the influence of leadership style on managerial performance, both directly and indirectly through work involvement and innovative work behavior that act as mediators. Design/methodology/approach – The theoretical model of the study was built on the basis of goal setting theory, namely that performance is a positive function of the goal achievement process. When performance can be controlled, specific goals will reduce performance variation by reducing ambiguity of achieved performance. Findings – The results reveal that leadership style has a significant effect on work involvement and innovative behavior. Likewise, work involvement and innovative behavior have a significant effect on managerial performance, but inversely proportional to the influence of leadership style does not affect managerial performance. Originality – The data were collected from all Account Representatives in all Pratama Tax Service Offices in South Sulawesi. The respondents were selected using the purposive sampling. Keywords: leadership style, managerial performance, work involvement, innovative work behavior, account representative, goal setting theory Paper Type Research Result